KEANEKARAGAMAN HASIL TANGKAPAN GOMBANG PADA SIANG DAN MALAM HARI DI DESA PANGKALAN JAMBI KABUPATEN BENGKALIS PROVINSI RIAU - Rianti, Annisa; Heltria, septy; Gelis, Ester Restiana Endang; Sumadja, Wiwaha Anas; Depison, Depison; Roiska, Riris (JURNAL PERIKANAN TROPIS, 2025)
Filter net is a traditional fishing gear designed as a conical bag with small-mesh netting. It operates as a passive tool, intercepting and trapping fish by leveraging the velocity of tidal currents. This study investigates the diversity and comparison of catch yields between daytime and nighttime in Pangkalan Jambi Village, Bengkalis Regency, Riau Province. Data collection consisted of fishermen's catch records. The research employed a survey method with direct field observations. The results revealed that the catch composition of the filter net in Pangkalan Jambi Village comprised 32 species. Daytime catches totalled 5,695 individuals, while nighttime catches amounted to 6,414 individuals. Commonly caught species during both daytime and nighttime included kedukang fish, lomek fish, biang fish, spiny shrimp, red shrimp, and jerbung shrimp. T-test results indicated no significant difference in catch quantities between daytime and nighttime (P > 0.05). The study concluded that the diversity index for daytime and nighttime catches was moderate, the evenness index was high, and the dominance index was low. The frequency of occurrence of the primary catch species during daytime and nighttime exceeded 50%.